Glycan chains of gangliosides: functional ligands for tissue lectins (siglecs/galectins) - Ledeen, Robert W.; Kopitz, Jürgen (Progress in molecular biology and translational science, 2018)
Molecular signals on the cell surface are responsible for adhesion and communication. Of relevance in this respect, their chemical properties endow carbohydrates with the capacity to store a maximum of information in a minimum of space. One way to present glycans on the cell surface is their covalent conjugation to a ceramide anchor. Among the resulting glycosphingolipids, gangliosides are special due to the presence of at least one sialic acid in the glycan chains. Their spatial accessibility and the dynamic regulation of their profile are factors that argue in favor of a role of glycans of gangliosides as ligands (counterreceptors) for carbohydrate-binding proteins (lectins). Indeed, as discovered first for a bacterial toxin, tissue lectins bind gangliosides and mediate contact formation (trans) and signaling (cis). While siglecs have a preference for higher sialylated glycans, certain galectins also target the monosialylated pentasaccharide of ganglioside GM1. Enzymatic interconversion of ganglioside glycans by sialidase action, relevant for neuroblastoma cell differentiation and growth control in vitro, for axonogenesis and axon regeneration, as well as for proper communication between effector and regulatory T cells, changes lectin-binding affinity profoundly. The GD1a-to-GM1 “editing” is recognized by such lectins, for example, myelin-associated glycoprotein (siglec-4) losing affinity and galectin-1 gaining reactivity, and then translated into postbinding signaling. Orchestrations of loss/gain of affinity, of ganglioside/lectin expression, and of lectin presence in a network offer ample opportunities for fine-tuning. Thus glycans of gangliosides such as GD1a and GM1 are functional counterreceptors by a pairing with tissue lectins, an emerging aspect of ganglioside and lectin functionality.